Approximate analytic expression for the eigenenergies of the anharmonic oscillator V(x)=Ax6+Bx2 - Dutra, Alvaro de Souza [UNESP]; De Castro, A. S. [UNESP]; Boschi-Filho, H. (American Physical Soc, 1995)
An approximate analytic expression for the eigenenergies of the anharmonic oscillator V(x)=Ax6+Bx2 is introduced, starting from particular analytic solutions which are valid when certain relations between the parameters A and B are held. © 1995 The American Physical Society.